Modern and Effective Methods of Training Teachers in our Country - Komiljonovna, Isabayeva Dilfuza (European Journal of Life Safety and Stability (2660-9630), 2022)
To date, the system of education in secondary and higher education institutions in our country is becoming very weak, and this leads to a very urgent topic. This decline of the education system is evidence of a lack of pedagogues. In this article of ours, we will teach how to train pedagogues, that is, how to train, and an effective way to train pedagogues with modern thinking in our country.